ANALYSING RESTORATIVE APPROACHES IN PUBLIC HEALTH CONFLICTS - Widjaja, Gunawan (CV. Lafadz Jaya, 2025)
Restorative approaches in public health conflict offer solutions that focus on restoring social relations and peacefully resolving conflict through inclusive dialogue. This method provides space for all parties involved to actively participate, identify root causes, and seek solutions together to minimise the negative impact of conflict on the public health system. Compared to traditional retributive approaches, restorative approaches emphasise social justice, open communication and collective healing, making them more effective in building trust and improving responsiveness to community health needs. The implementation of this approach not only resolves the conflict, but also helps to create a more resilient and sustainable public health system.